2009
DOI: 10.1037/a0013746
|View full text |Cite
|
Sign up to set email alerts
|

Getting off on the right foot: Subjective value versus economic value in predicting longitudinal job outcomes from job offer negotiations.

Abstract: Although negotiation experiences can affect a negotiator's ensuing attitudes and behavior, little is known about their long-term consequences. Using a longitudinal survey design, the authors tested the degree to which economic and subjective value achieved in job offer negotiations predicts employees' subsequent job attitudes and intentions concerning turnover. Results indicate that subjective value predicts greater compensation satisfaction and job satisfaction and lower turnover intention measured 1 year lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 72 publications
8
79
0
Order By: Relevance
“…To test the theory that SV can have important long‐term consequences in real‐world settings, Curhan, Elfenbein, and Kilduff (2009) examined longitudinally the roles played by objective and subjective value achieved at the time of job‐offer negotiations in predicting employees' subsequent job attitudes and turnover intentions 1 year later. The results indicated that SV from job‐offer negotiations predicted greater subsequent compensation satisfaction and job satisfaction, and lower subsequent turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…To test the theory that SV can have important long‐term consequences in real‐world settings, Curhan, Elfenbein, and Kilduff (2009) examined longitudinally the roles played by objective and subjective value achieved at the time of job‐offer negotiations in predicting employees' subsequent job attitudes and turnover intentions 1 year later. The results indicated that SV from job‐offer negotiations predicted greater subsequent compensation satisfaction and job satisfaction, and lower subsequent turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the negotiation literature's focus on economic outcomes, they are but one measure of negotiator success (Curhan, Elfenbein, & Kilduff, 2009). Other outcomes, including satisfaction with the experience also matter to negotiators (Curhan, Elfenbein, & Xu, 2006).…”
Section: Hypothesesmentioning
confidence: 99%
“…Empirical work shows tangible performance consequences to high SV in terms of future economic gain, stronger professional relationships for the future, and even job satisfaction among employees (Curhan, Elfenbein, & Kilduff, 2009;Tinsley, O'Connor, & Sullivan, 2002). Subjective value has two theoretically distinct conceptualizations: the perceptions of the negotiator and the perceptions of the counterpart.…”
mentioning
confidence: 97%